Relações bioquímicas e moleculares da germinação e emergência em arroz - Malone, Gaspar (2007)
In this work, a collection of red rice ecotypes, with promising physiological characteristics associated to seed vigor, was used to conduct three studies to understand the germination/emergence process in rice. In the first study, a biochemical and molecular characterization of the collection was performed to identify the parent s with the best hybrid potential to obtain segregant mapping populations. In the second study, the AMY1 α-amylase gene of rice, involved in the breakdown of endosperm starch during germination, was analyzed by DNA sequencing, to identify mutants to this gene from red rice ecotypes. The mutation effects were analyzed thought physiological performance of ecotypes. In the last study, an segregant population from FFS-45 red rice ecotype (with germination/emergence character) and BRS 7 taim cultivar (without the character), was used to identify molecular markers linked to the trait by DNA Pooling methodology. The molecular markers identified were used to gene prospection in the respective genomics regions. Five SSR markers were identified linked to germination/emergence process. Results of these researches generated a great amount of data that can be contribute to understand the physiological/molecular process involved in rice seed germination/emergence process.